2016
DOI: 10.1002/lary.26303
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of eosinophilic otitis media with pegylated interferon‐α 2a and 2b

Abstract: 4. Laryngoscope, 127:1208-1216, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The role of surgery in the treatment of this disease appears to be limited. No surgical treatment has demonstrated consistent improvement, but removal of granulation tissue may provide symptomatic relief and make topical treatments more effective (1,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of surgery in the treatment of this disease appears to be limited. No surgical treatment has demonstrated consistent improvement, but removal of granulation tissue may provide symptomatic relief and make topical treatments more effective (1,24).…”
Section: Discussionmentioning
confidence: 99%
“…Our data build on growing evidence that control of the underlying eosinophilia is often necessary for symptomatic improvement of eosinophilic otitis media. For example, aggressive asthma control has also been shown to provide clinical improvement (22,23) as has treatment with pegylated interferon-α 2a or 2b and ramatroban (24). The role of surgery in the treatment of this disease appears to be limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed a satisfactory clinical response, with complete resolution of otorrhea, normalization of the middle ear mucosa and discontinuation of corticosteroid therapy in 50% of the cases. 38 Considering these facts, the aim of the present study was to investigate in vitro whether IFN-α alters the cytokine profile of eosinophilic CRSwNP, which is known to have a predominant Th2 pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic and topical corticosteroids have been the main treatments for EOM because of their effectiveness. Recently, recombinant humanized monoclonal anti-IgE antibody therapy (omalizumab) [ 31 ] and pegylated interferon [ 32 ] have been reported to be effective for EOM. Omalizumab improves the subjective symptoms and clinical characteristics, and pegylated interferon also improves the clinical findings.…”
Section: Discussionmentioning
confidence: 99%